Findings of remote monitoring of implantable cardioverter defibrillators during the COVID‐19 pandemic. Issue 11 (26th October 2020) - De Larochellière, Hugo; Champagne, Jean; Sarrazin, Jean‐François; Steinberg, Christian; Philippon, François; Roy, Karine; Molin, Franck; O'Hara, Gilles; Plourde, Benoit; Blier, Louis; Nault, Isabelle
Abstract: Background: Monitoring of cardiac implantable electronic devices was highly impacted by the COVID‐19 pandemic considering the high volume of in‐person visits for regular follow‐up. Recent recommendations highlight the important role of remote monitoring to prevent exposure to the virus. This study compared remote monitoring of implantable cardioverter defibrillators (ICDs) in patients whose in‐person annual visit was substituted for a remote monitoring session with patients who were already scheduled for a remote monitoring session. Methods: This was a cross‐sectional observational study of 329 consecutive patients between 20 March and 24 April 2020. Group 1 included 131 patients whose in‐person annual visit was substituted for a remote monitoring session. Group 2 included 198 patients who underwent a remote monitoring session as scheduled in their usual device follow‐up. The time interval since the last in‐person visit was 13.3 ± 3.2 months in group 1 and 5.9 ± 1.7 months in group 2 ( P  < .01). Results: In group 1, 15 patients (11.5%) experienced a clinical event compared to 15 patients (7.6%) in group 2 ( P  = .25). Nineteen patients (14.5%) required a physician intervention in group 1 compared to 19 patients (9.6%) in group 2 ( P  = .22). Two patients (1.5%) in group 1 and four patients (2.0%) in group 2 required an early in‐person follow‐up visit during the pandemic ( P  > .99). Conclusion: Remote monitoring of ICDs is useful to identify clinical events and allows physicians to treat patients appropriately during the COVID‐19 pandemic regardless of the time interval since their last in‐person visit. It reduces significantly in‐person visit for regular follow‐up.